Утицај броја нуклеираних црвених крвних зрнаца седмог дана на морталитет код пацијената одељења интензивне неге Цовид-19: ретроспективна студија контроле случајева: Nucleated RBCs in COVID-19 - DÜZ, Muhammed Emin; ARSLAN, Mustafa; MENEKŞE, Elif; AVCI, Burak Yasin (Journal of Medical Biochemistry, 2022)
Objective COVID-19 covers a broad clinical spectrum, threatening global health. Although several studies have investigated various prognostic biochemical and hematological parameters, they generally lack specificity and are insufficient for decision-making. Beyond the neonatal period, NRBCs (nucleated red blood cells) in peripheral blood is rare and often associated with malignant neoplasms, bone marrow diseases, and other severe disorders such as sepsis and hypoxia. In addition, NRBCs can predict mortality in hypoxic ICU patients like COVID-19, similar to other diseases. Materials and Methods Seventy-one unvaccinated RT-PCR confirmed COVID-19 ICU patients was divided into those who survived (n=35, mean age=58) and died (n=36, mean age=75). NRBC numbers and percentages of the patients were compared on the first and seventh days of admission to the ICU. Results are reported as a proportion of NRBCs per 100 WBCs [NRBCs/ 100 WBC (NRBC%) and as absolute NRBC count (NRBC #, × 109 /L). Results NRBC 7th-day count and % values were statistically higher in non-survival ones. The sensitivity for 7th day NRBC value <0.01 (negative) was 86.11%, the specificity was 48.57%, for <0.02; 75.00%, and 77.14%, for <0.03; 61.11%, and 94.60%. Conclusion In conclusion, we indicate that NRBC elevation (>0.01) significantly predicts mortality in ICU hospitalized patients due to COVID-19. Worse, a high mortality rate is expected, especially with NRBC values of >0.03.